The Modified Lemaire Procedure - Christoph Kittl MD, MD (Res); Michael Wagner MD; Andreas Weiler MD, PhD (SAGE Publishing, 2022)
Background: Anterolateral rotatory instability (ALRI) may be one reasons why anterior cruciate ligament (ACL) reconstructions fail. An additional reconstruction of the anterolateral structures reduces the graft rupture rate by 50%. The modified Lemaire procedure is one of the lateral extra-articular tenodeses (LET) to restrain ALRI. The purpose of the present video is to describe this technique in detail. Indications: According to the international anterolateral complex consensus group indications may include revision ACL reconstruction, high grade pivot shift, generalized ligamentous laxity, like genu recurvatum, and young patients returning to pivoting activities. However, clinical evidence to recommend specific indications is still missing. Technique description: A 7 to 10 mm wide strip of the iliotibial tract, attached to Gerdy tubercle is shuttled deep to the lateral collateral ligament and is then attached proximal to the lateral femoral epicondyle. The biomechanical principle behind this is to place the graft posterior to the transverse axis of rotation through the entire range of motion. This posterior pull will restrain internal rotation and the anterior subluxation of the lateral tibial plateau. Results: Newer comparative studies show a reduced graft rupture rate and higher rate of returning to preinjury level, when adding an anterolateral extra-articular reconstruction to the ACL reconstruction at 2 years follow-up. At long-term follow-up there was also a trend toward decreased graft rupture rate. However, one must be aware of the possible increased risk of lateral compartment osteoarthritis. Conclusion: The modified Lemaire procedure is an easy-to-use addon to the ACL reconstruction, which can effectively reduce graft failure rate.